Who's included? a survey of poverty in Guyana ([Caribbean Conference of Churches] BridgetownBB, 1993)
Seeks to identify practical ways in which a normative framework for development can be promoted by the churches in Guyana and the Caribbean as their major contribution to the resolution of poverty in this region. Looks at Guyana in a global context; poverty in Guyana; a response to poverty in Guyana by the churches; and an action programme for the churches.
DC